Direct measurement of carbon nanotube temperature between fiber ferrules as a universal tool for saturable absorber stability investigation. (30th October 2021) - Galiakhmetova, Diana; Gladush, Yuriy; Mkrtchyan, Aram; Fedorov, Fedor S.; Khabushev, Eldar M.; Krasnikov, Dmitry V.; Chinnambedu-Murugesan, Raghavan; Manuylovich, Egor; Dvoyrin, Vladislav; Rozhin, Alex; Rümmeli, Mark; Alyatkin, Sergey; et al.
Abstract: Single-walled carbon nanotubes (SWCNTs) are widely explored for the ultrashort pulse generation in the fiber lasers enabled by pronounced saturable absorption (SA) effect. Despite many remarkable results demonstrated in the area, degradation of the samples inside the laser cavity limits the widespread use of SWCNT-SA. In the present work, we investigate the degradation mechanism by measuring the temperature of the carbon nanotubes in an operating laser cavity in accordance with the Raman G-band position. We identify the process behind the sample degradation by comparing the burning temperature of the sample with results of thermogravimetric analysis. We apply this approach for the SWCNTs in polyvinyl alcohol polymer matrix and polymer-free SWCNT thin film and demonstrate that these samples undergo different degradation mechanism. Proposed technique provides a useful instrument for optimization of SWCNT-SA for desired ultrafast laser generation. Graphical abstract: Image 1